2022
DOI: 10.21203/rs.3.rs-2099391/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing multi-environment testing in potato breeding: using heritability estimates to determine number of replications, sites, and years for field trials

Abstract: Multi-environment trials (METs) of potato breeding clones and cultivars allow to precisely determine their genetic values. However, these METs may be affected by the genotype ´ environment interaction (GEI) as noted in tuber yield. Hence, the objectives of this research were to use components of variance from METs to estimate broad sense heritability (H2) based on best linear unbiased predictors and use these estimates to determine the optimum number of sites, years, and replications for testing potato breedin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For this trait, recently Ortiz et al. (2023) demonstrated that a sample size of experiments conducted across 10 locations, over 2 years per location, with four plots per genotype, is quite appropriate for estimating this characteristic and its heritability.…”
Section: Methodsmentioning
confidence: 99%
“…For this trait, recently Ortiz et al. (2023) demonstrated that a sample size of experiments conducted across 10 locations, over 2 years per location, with four plots per genotype, is quite appropriate for estimating this characteristic and its heritability.…”
Section: Methodsmentioning
confidence: 99%